Werkstoffgerechte Auslegung von Direktverschraubungen in SMC/BMC Bauteilen - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Werkstoffgerechte Auslegung von Direktverschraubungen in SMC/BMC Bauteilen - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Vergleich experimenteller Methoden zur Untersuchung des Aufschmelzprozesses in Einschneckenextrudern - Knaup, Felix; Brüning, Florian (Extrusion)
Keywords: Aufschmelzen; extrusion; Messtechnik

Thermo-Chemical Devulcanization of Sulfur-Cured Styrene-Butadiene Rubber (SBR) Using Diphenyldisulfide (DPDS) - Petzke, Jonas Dirk Rudolf Helmut; Schöppner, Volker

Influence of Filler Type and Volume Fraction on the Electrical Conductivity and Shore Hardness of TPU Composites in Fused Filament Fabrication - Moritzer, Elmar; Salm, Maximilian Karl Franz (The 40th International Conference of Polymer Processing Society)

Non-destructive fiber-matrix adhesion measurement of glass fiber reinforced thermoplastic composite laminates using ultrasound - Moritzer, Elmar; Brandes, Philipp; Wittler, Maurice; Claes, Leander; Wippermann, Mareen; Henning, Bernd (40th International Conference of the Polymer Processing Society)
Keywords: Faser-Kunststoff-Verbunde (FKV); Faserverstärkte Kunststoffe (FVK); Organobleche; Ultraschall

Experimental Analysis of the Mixing Behavior of Ethylene-Propylene-Diene Rubber (EPDM) in a Rubber Pin Extruder under Variation of Process Parameters and Mixing Elements - Petzke, Jonas Dirk Rudolf Helmut; Schmidt, Leon; Kleinschmidt, Dennis; Brüning, Florian (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: distributives Mischen; Extrusion; Kautschuk; Stiftextruder

Numerical modeling of the non-isothermal viscoelastic flow behavior of rubber compounds based on the PHAN-THİEN-TANNER (PTT) model - Damanik, Hogenrich; Fatima, Arooj; Turek, Stefan; Petzke, Jonas Dirk Rudolf Helmut; Kleinschmidt, Dennis; Brüning, Florian (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: CFD simulation; Materialmodellierung; Phan-Thien-Tanner; PTT; Simulation

Thermo-Chemical Devulcanization of Sulfur-cured Styrene-Butadiene Rubber (SBR) Using Diphenyldisulfide (DPDS) - Petzke, Jonas Dirk Rudolf Helmut; Kleinschmidt, Dennis; Brüning, Florian (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: Devulkanisation; Kautschuk; Recycling

Investigations into the specific throughput stability of conical feed zones over the rotation speed during the direct processing of polypropylene regrind - Rempel, Timm; Brüning, Florian (ANTEC)

Devulcanization behavior of SBR-based GTR compounds - Petzke, Jonas Dirk Rudolf Helmut

Intrinsic lubrication: A new approach in the context of the deep drawing process - Cakici, Ermir; Homberg, Werner (Materials Research Proceedings)
Abstract. This study presents intrinsic lubrication as a novel approach to deep drawing processes, using additively manufactured, lubricant-permeable tools to minimize lubricant consumption and improve efficiency. Two systems were evaluated: a passive system based on capillary action and gravity, and an active system using pumped delivery for precise, on-demand application. Experimental tests were conducted on micro-bores (0.2-0.5 mm) to demonstrate their suitability for lubricant transport. Smaller bores have excellent capillary action but are prone to clogging, while larger bores offer higher permeability. The passive system is resource-efficient but requires adjustments to counteract gravitational asymmetry. The active system provides consistent lubricant distribution but is more complex. These findings provide a basis for optimizing intrinsic lubrication systems.

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, Moritz; Holtkamp, Pia Katharina; Hoyer, Kay-Peter; Kappe, Fabian; Yildiz, Safak; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (The Journal of Materials: Design and Applications, Part L)
One of the most important strategies for reducing CO2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.
Keywords: aluminium; casting; microstructure; joinability; self-piercing riveting

Validation and Verification of Novel Three-Dimensional Crack Growth Simulation Software GmshCrack3D - Krome, Sven; Duffe, Tobias; Kullmer, Gunter; Schramm, Britta; Ostwald, Richard (Applied Sciences)
The accurate prediction of crack initiation and propagation is essential for assessing the structural integrity of mechanically joined components and other complex assemblies. To overcome the limitations of existing finite element tools, a modular Python framework has been developed to automate three-dimensional crack growth simulations. The program combines geometric reconstruction, adaptive remeshing, and the numerical evaluation of fracture mechanics parameters within a single, fully automated workflow. The framework builds on open-source components and remains solver-independent, enabling straightforward integration with commercial or research finite element codes. A dedicated sequence of modules performs all required steps, from mesh separation and crack insertion to local submodeling, stress and displacement mapping, and iterative crack-front update, without manual interaction. The methodology was verified using a mini-compact tension (Mini-CT) specimen as a benchmark case. The numerical results demonstrate the accurate reproduction of stress intensity factors and energy release rates while achieving high computational efficiency through localized refinement. The developed approach provides a robust basis for crack growth simulations of geometrically complex or residual stress-affected structures. Its high degree of automation and flexibility makes it particularly suited for analyzing cracks in clinched and riveted joints, supporting the predictive design and durability assessment of joined lightweight structures.

Zerstörungsfreie Ultraschall-Prüfung von Organoblechen - Moritzer, Elmar; Brandes, Philipp; Westphal, Max Siegfried; Claes, Leander; Wippermann, Mareen; Düchting, Julia; Henning, Bernd (WAK Jahresmagazin)
Keywords: Faser-Kunststoff-Verbunde (FKV); Faserverstärkte Kunststoffe (FVK); Organobleche; Ultraschall

Influence of different oxide thicknesses on the friction induced and continuous solid-state recycling of aluminum scrap - Gabsa, Steffen; Homberg, Werner; Goller, Timothy; Nordieker, Ansgar Bernhard; Grundmeier, Guido (Materials Research Proceedings)
Abstract. Saving emissions and a circular economy are key aspects of sustainable production and compliance global climate change targets. Friction-induced solid-state recycling of aluminum scrap to production endless semi-finished products. Scrap is fed into a continuously rotating wheel. This requires less energy compared to heat-based recycling processes. Different sizes, shapes and surfaces of chips can be used as starting material in the process. The influence of this has been shown in past publications. A native oxide layer is a fixed component of aluminum surface. This layer is broken up during the forming process, allowing the aluminum to bond. In addition to the geometry, the surface finishes and the thickness of the oxide layer are therefore also important input variables in friction-induced solid-state recycling. The oxide layers on the chips were determined for the investigation. In addition, different layer thicknesses were produced to survey their influence. The resulting semi-finished products were evaluated on the basis of their tensile strength and microstructure. The main result of the investigations is the fact that semi-finished products made from chips with thicker oxide layers tend to be more brittle. In addition, thick oxide layers cause microstructural and surface defects.

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor
Die Extrusion stellt das mengenmäßig dominante Verarbeitungsverfahren für thermoplastische Kunststoffe dar. Daher gibt es starke Bestrebungen in diesem Bereich hin zu einer höheren Wirtschaftlichkeit, welche beispielsweise durch höheren Massedurchsatz bei gleichbleibender Maschinengröße erreicht werden kann, oder aber auch im Hinblick auf eine Kreislaufwirtschaft die Bestrebung hin zu einer materialschonenden Verarbeitung. Beide Bestrebungen erfordern spezielle Schneckenkonzepte. Hierunter fallenWave- Schnecken, welche in beiden Bereichen ein vorteilhaftes Prozessverhalten aufzeigen sollen. Die Auslegung von Wave-Schnecken erfordert jedoch ein stärkeres Verständnis über das geometrieabhängige Prozessverhalten in der Extrusion. Im Rahmen der Dissertation werden zwei Themengebiete angegangen. Das erste Thema ist die Herleitung einer Methode zur Charakterisierung des Abbauverhaltens von Thermoplasten sowie die Nutzung der Charakterisierung als Vorhersagemodell. Das zweite Thema behandelt die Auslegung von Wave-Schnecken basierend auf numerischen Simulationen samt Validierung anhand von sieben Energy-Transfer-Schnecken im Vergleich zu drei konventionellen Schnecken. Hierbei werden unter anderem der Materialabbau, die thermische und die stoffliche Homogenität betrachtet, um ein umfassendes Bild über das Prozessverhalten der Schnecken zu schaffen. Die vorgestellten Untersuchungen dienen schlussendlich zu einer Bestätigung des vorteilhaften Prozessverhaltens von Wave-Schnecken.

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Multiscale simulation of polymer curing of composites combined mean-field homogenisation methods at large strains - Lenz, Peter; Mahnken, Rolf (International Journal of Solids and Structures)
Keywords: Applied Mathematics; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation